Cerebral regional tissue Oxygen Saturation to Guide Oxygen Delivery in preterm neonates during immediate transition after birth (COSGOD III): multicentre randomised phase 3 clinical trial. (24th January 2023) - Pichler, Gerhard; Goeral, Katharina; Hammerl, Marlene; Perme, Tina; Dempsey, Eugene M; Springer, Laila; Lista, Gianluca; Szczapa, Tomasz; Fuchs, Hans; Karpinski, Lukasz; Bua, Jenny; Avian, Alexander; et al.
Abstract: Objective: To investigate whether monitoring of cerebral tissue oxygen saturation using near infrared spectroscopy in addition to routine monitoring combined with defined treatment guidelines during immediate transition and resuscitation increases survival without cerebral injury of premature infants compared with standard care alone. Design: Multicentre, multinational, randomised controlled phase 3 trial. Setting: 11 tertiary neonatal intensive care units in six countries in Europe and in Canada. Participants: 1121 pregnant women (<32 weeks' gestation) were screened prenatally. The primary outcome was analysed in 607 of 655 randomised preterm neonates: 304 neonates in the near infrared spectroscopy group and 303 in the control group. Intervention: Preterm neonates were randomly assigned to either standard care (control group) or standard care plus monitoring of cerebral oxygen saturation with a dedicated treatment guideline (near infrared spectroscopy group) during immediate transition (first 15 minutes after birth) and resuscitation. Main outcome measure: The primary outcome, assessed using all cause mortality and serial cerebral ultrasonography, was a composite of survival without cerebral injury. Cerebral injury was defined as any intraventricular haemorrhage or cystic periventricular leukomalacia, or both, at term equivalent age or before discharge. Results: Cerebral tissue oxygen saturation was similar in both groups. 252 (82.9%) out of 304 neonates (median gestational age 28.9 (interquartile range 26.9-30.6) weeks) in the near infrared spectroscopy group survived without cerebral injury compared with 238 (78.5%) out of 303 neonates (28.6 (26.6-30.6) weeks) in the control group (relative risk 1.06, 95% confidence interval 0.98 to 1.14). 28 neonates died (near infrared spectroscopy group 12 (4.0%) v control group 16 (5.3%): relative risk 0.75 (0.33 to 1.70). Conclusion: Monitoring of cerebral tissue oxygen saturation in combination with dedicated interventions in preterm neonates (<32 weeks' gestation) during immediate transition and resuscitation after birth did not result in substantially higher survival without cerebral injury compared with standard care alone. Survival without cerebral injury increased by 4.3% but was not statistically significant. Trial registration: ClinicalTrials.gov NCT03166722 .